Letter from James B. Guthrie to James Curtis Booth, April 5, 1854 - Guthrie, James (1854)
James B. Guthrie (1792 - 1869), United States Secretary of the Treasury from 1853-1857, requests James Curtis Booth (1810-1888) testify before the New York Board of Supervisory Inspectors of Steam Boats. Booth notes that he is unable to do so due to a scarcity of bismuth which had delayed his research.
Keywords: Guthrie, James, 1792-1869; Booth, James Curtis, 1810-1888; United States. Department of the Treasury; United States Mint; Mint of the United States; Alloys; Steamboats